Institutional quality and sovereign credit default swap spreads. Issue 6 (3rd January 2019) - Huang, Wei; Lin, Shu; Yang, Jian
Abstract: We examine how the quality of political, legal, and regulatory institutions impacts sovereign risk premia. An improvement in institutional quality significantly lowers a country's sovereign credit default swap (CDS) spread, even after controlling for domestic and global macroeconomic factors. The incremental effect of institutional quality may also be economically important in explaining the variations in the level of sovereign CDS spreads. The basic results are robust to alternative model specifications, samples, control variables, measures of institutional quality, estimation methods, and controls for endogeneity. Overall, the evidence suggests that institutional quality may play a significant role in explaining sovereign CDS spreads.